1993
DOI: 10.1111/j.1651-2227.1993.tb12698.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth hormone treatment on craniofacial growth in Turner's syndrome

Abstract: A cephalometric study was performed in 19 patients with Turner's syndrome, aged 8.7–16.5 years. A lateral roentgencephalogram was taken before and after two years of treatment with biosynthetic growth hormone in a dose of 24 IU/m2/week. During two years of growth hormone treatment, the mandibular length increased mainly due to vertical growth. The initially posteriorly rotated mandible showed an anterior rotation, although the normal position was not reached. The other linear measurements and angles did not ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 6 publications
3
39
0
4
Order By: Relevance
“…Both jaws were retrognathic, even though maxillary and mandibular body average length increased under the influence of GH therapy. These results are in accordance with previous studies that have also found retrognathic jaws [24][25][26] and increase in mandibular ramus [24][25][26] and corpus lengths 25,26 in TS girls treated with GH. Bimaxillar retrognathism, also present in TS girls 2,3,5-7 and adult patients 4,8 that were not treated with GH, used to be explained by flattened cranial base 3 and reduced lengths of maxilla and mandible.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Both jaws were retrognathic, even though maxillary and mandibular body average length increased under the influence of GH therapy. These results are in accordance with previous studies that have also found retrognathic jaws [24][25][26] and increase in mandibular ramus [24][25][26] and corpus lengths 25,26 in TS girls treated with GH. Bimaxillar retrognathism, also present in TS girls 2,3,5-7 and adult patients 4,8 that were not treated with GH, used to be explained by flattened cranial base 3 and reduced lengths of maxilla and mandible.…”
Section: Discussionsupporting
confidence: 83%
“…The growth of mandibular ramus under the influence of GH treatment causes anterior rotation of mandible in TS patients, 24,26 as well as in idiopathic short stature boys and GH deficient boys. 18 Similarly, in this study mandibular ramus height was found to be significantly larger in TS patients treated with GH compared to healthy controls and also overdeveloped in comparison to mandibular corpus length.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations